Viral metagenomics of pharyngeal secretions from children with acute respiratory diseases with unknown etiology revealed diverse viruses - Qingqing Mao; Guangming Sun; Yu Qian; Yuchen Qian; Wang Li; Xiaochun Wang; Quan Shen; Shixing Yang; Chenglin Zhou; Hao Wang; Wen Zhang (Virus Research, 2022)
Acute respiratory tract infections are a major public health problem and the leading cause of morbidity in children younger than 5 years old. This study investigated the potential reasons of unexplained acute respiratory infections in children in Xuzhou and its environs during 2018-2019.We collected pharyngeal swab samples from 411 children under the age of five who presented with symptoms of unexplained acute respiratory infection and were negative for bacteria, mycoplasma, and influenza viruses. Using viral metagenomic techniques, viral nucleic acids were extracted, enriched, and sequenced from the samples. Results indicated that Picornaviridae, Parvoviridae, Paramyxoviridae, Coronaviridae, and Anelloviridae were the five virus families with the highest relative content of sequence reads. And we detected 35 HBoV-positive and 12 HEV-positive samples out of 411 samples by the polymerase chain reaction (PCR). Partial or nearly complete genome sequences of viruses belonging to the families Picornaviridae, Parvoviridae, and Anelloviridae were characterized, and phylogenetic trees were constructed based on the nucleic acid or amino acid sequences of the predicted viral open reading frames (ORFs), as well as genotyping of the viruses. In addition, we observed recombination events in the Saffold virus and Coxsackievirus A9 by analyzing the genetic characteristics of the viruses revealed in this study. This study provides vital information for the prevention and treatment of acute respiratory infections in children younger than five years old.